Effects of long‐term elevation of air temperature on sucrose metabolism in cotton leaves at different positions. (20th July 2017) - Hu, W.; Dai, Y.; Zhao, W.; Meng, Y.; Chen, B.; Wang, Y.; Zhou, Z.
Abstract: Global warming could possibly increase the air temperature by 1.8–4.0°C in the coming decade. To forecast the effects of long‐term elevation of air temperature on sucrose synthesis in cotton leaves at different positions, field experiments with the treatments of ambient temperature (control) and elevated temperature (2–3°C) across cotton's boll forming stage were conducted in 2011 and 2012. Results showed that sucrose content in the fourth main‐stem leaves from the terminal (FMLT) during 10–17 days after treatment (DAT) and in the leaves subtending the cotton boll (LSCB) during 17–45 days post‐anthesis (DPA) was lower in the increased temperature treatment than control treatment, but starch content was higher, resulting in higher specific leaf weight (SLW). Lower sucrose content might be attributed to low ribulose‐1, 5‐bisphosphate carboxylase‐oxygenase (Rubisco) and cytosolic fructose‐1, 6‐bisphosphatase (cy‐FBPase) activities under elevated temperature for all tested leaves. Comparison of different fruiting branch (FB) positions, sucrose transformation rate just decreased in LSCB growing on FB2–3 and FB6–7 . Compared with FB10–11, the leaves at FB2–3 and FB6–7 were more sensitive to the increased temperature, showing as that the changing amplitudes of SLW, sucrose content, starch content, initial Rubisco activity and cy‐FBPase activity were greater. Regarding different types of cotton leaves, the effects of elevated temperature on sucrose content, starch content and initial Rubisco activity in FMLT were obvious at the early stage (10–17 DAT), but were not obvious at the late stage. However, the effects were consistent in LSCB from 17 to 45 DPA. In addition, long‐term elevated temperature had smaller impacts on above indices in FMLT than LSCB. Sucrose phosphate synthase (SPS) and sucrose synthase (SuSy) activities were decreased by elevated temperature in FMLT at the early stage, but were increased in LSCB, suggesting that SPS and SuSy were the key enzymes between FMLT and LSCB in response to elevated temperature.